2011
DOI: 10.1007/s00417-011-1842-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of retinal vessel response to flicker light in glaucoma patients and ocular hypertensives

Abstract: Purpose To analyze dynamics of retinal vessel dilation response to flicker light in patients with glaucoma and ocular hypertension. Patients and methods Response to flicker light was measured in retinal vessels by means of Retinal Vessel Analyzer. After the baseline 50 seconds long diameter recording of inferior and superior temporal artery and vein, three flicker stimulations of 20 seconds duration was applied, with a 80 seconds break in between. Area under the curve of the vessel diameter (AUC) was compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 17 publications
3
61
1
1
Order By: Relevance
“…Numerous groups have examined its potential for diagnostic applications in diabetes, [1][2][3][4][5] cardiovascular disease, 6,7 and glaucoma [8][9][10] (see Heitmar and Summers 11 for a review). Over time a standard protocol has emerged comprising 50 seconds baseline measurement (continuous illumination) followed by three cycles of 20 seconds, 12.5 Hz FL, and 80 seconds recovery (total measurement time ¼ 350 seconds).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous groups have examined its potential for diagnostic applications in diabetes, [1][2][3][4][5] cardiovascular disease, 6,7 and glaucoma [8][9][10] (see Heitmar and Summers 11 for a review). Over time a standard protocol has emerged comprising 50 seconds baseline measurement (continuous illumination) followed by three cycles of 20 seconds, 12.5 Hz FL, and 80 seconds recovery (total measurement time ¼ 350 seconds).…”
mentioning
confidence: 99%
“…Additionally baseline diameter fluctuation (peakto-trough amplitude prior to flicker onset), dilation amplitude (difference between maximum and minimum dilation), and time to reach maximum dilation can also be assessed and this set of five parameters is sometimes termed sequential diameter response analysis (SDRA) 16 ; though note other forms of analysis have been attempted. 9,17,18 The aim of this study was firstly to evaluate how FL duration affected the various SDRA parameters; for example, how is maximum dilation/ maximum constriction affected by flicker duration? The second goal was to evaluate individual flicker cycles and assess the variability in SDRA parameters across flicker cycles in protocols of different FL duration.…”
mentioning
confidence: 99%
“…17,18 Flicker-induced vasodilation of retinal and ONH vessels is appreciably reduced in glaucoma patients, indicating important neurovascular coupling defects in this disease. 19,20 A relationship between glaucoma and endothelin, a potent vasoactive peptide, has also been established. Elevated plasma and aqueous humor levels of endothelin have been detected in normal tension and primary open-angle glaucoma patients, [21][22][23][24] and endothelin receptor inhibition increases ocular blood flow in individuals with glaucoma.…”
mentioning
confidence: 99%
“…As such, it has been shown that flicker-induced vasodilation is reduced in early-and late-stage diabetic retinopathy (Garhofer et al 2004a,b,c;Mandecka et al 2007;Nguyen et al 2009a,b;Pemp et al 2009;Lasta et al 2013), in patients with early-stage glaucoma (Garhofer et al 2004a,b,c;Gugleta et al 2012) and in patients with systemic hypertension (Nagel et al 2004). …”
Section: Discussionmentioning
confidence: 99%